Digital Transformation in the Bureaucracy of Kuningan Regency: Achieving Efficient and Transparent Public Services - Kamila, Nabila; Buchari, Rd Ahmad; Widianingsih, Ida; Abdillah, Abdillah (Iapa Proceedings Conference, 2024)
This study examines the role of digital transformation in enhancing bureaucratic efficiency and transparency in Kuningan Regency. As public expectations for faster, more transparent services grow, the local government is adopting various digital technologies, including e- government platforms, to improve service delivery. Using a case study methodology, this research assesses the implementation of digital tools in streamlining administrative processes and fostering better public access to government information. The findings indicate that while digital transformation has significantly increased operational efficiency, challenges such as digital literacy gaps, infrastructural constraints, and resistance to technological change continue to hinder full adoption. The study concludes by recommending targeted policy interventions to overcome these obstacles, ensuring that digital governance not only increases service efficiency but also strengthens accountability and trust in the public administration of Kuningan. This paper contributes to the understanding of how local governments in developing regions can effectively implement digital reforms to modernize bureaucracy and meet the demands of a digital age.